The Contribution of Community Education towards Minimizing the Spread of COVID-19: Ethnographic Research Approach - Mabade, Avhurengwi Samson (Advances in Social Sciences Research Journal, 2021)
Although the Government put protocols in place to minimize the spread of COVID-19, it remains the community’s obligation to adhere to the protocols and drive reform. It is the community’s responsibility to communicate succinctly and elegantly all the protocols in a morally unobjectionable manner. It is however a community-based problem although it is a worldwide pandemic to be fought holistically. Unless an individual community understands the impact of COVID-19 in the community, community members would hardly understand its impact in the entire community. If community members could heed the super spreading ways, almost all community members would advise one another on the best ways to mitigate the spread of this pandemic. The transformation brought about by community itself would result the transformation of each community member. Community leadership remains responsible to advocate this community education. The researcher adopted an Ethnographic Research Approach to provide an in-depth description of community members towards adhering to the protocols in place for minimizing the spread of this horrifying and deadly disease. The researcher employed qualitative technique for the collection of data. The responses of the community members were audio recorded and transcribed by the researcher and then analyzed for presentation as a report.